Paul Natorp and the Psychologismus-Streit - Pelegrin, Laura (Argumentos - Revista de Filosofia, 2025)
The aim of this paper is to exhibit the core of Paul Natorp's criticisms of psychologism. We expose the arguments that lead Natorp to conclude that knowledge cannot have a subjective foundation but must have an objective grounding. We argue that, according to Natorp, the problem of psychologism is fundamentally methodological. Psychologism confuses the study of the laws of knowledge with the study of the legality of psychical life. Thus, the problem of the genesis is confused with the problem of validity.